The Effect of Halal Certification, Product Quality and Price on the Purchase Decision of Make Over Cosmetics in Semarang Regency with Brand Image as an Intervening Variable - Wandhini, Amalia Fiqia; Utomo, Budi (LPPM Universitas Bina Bangsa, 2024)
This study aims to determine the influence of halal certification, product quality and price on the purchase decision of Make Over products with brand image as an intervening variable. The research method used is quantitative using primary data. The research sample was 130 respondents who used Make Over products in Semarang Regency. The test uses path analysis to test the influence of intervening variables used to assess the relationship between three or more variables. The analysis tool used is SPSS 20. The results of the study show that simultaneously the variables of Halal Certification, Product Quality and Price have a significant positive effect on the brand image. However, halal certification and brand image have no effect on purchasing decisions, while product quality and price have a significant positive effect on purchasing decisions. Halal certification, product quality, and price do not have a significant effect on the purchase decision of Make Over products in Semarang Regency with brand image as an intervening variable